Mechanism of Protective Effect of Mongolia Medicine Nagab-9 on LPS-Induced Acute Lung Injury Based on an Integrated Network Pharmacology and Experimental Verification - Shi Liu; Jiuwang Yu; Zeyu Chen; Lidao Bao (Dose-Response)
Objectives To investigate the potential mechanisms of Nagab-9 in alleviating acute lung injury (ALI) by integrating network pharmacology analysis with in vivo and in vitro validation experiments. Methods Active compounds of Nagab-9 were identified using TCMSP and ETCM databases. ALI-related targets were collected from relevant disease databases, and an intersection of these targets was used to construct a protein-protein interaction (PPI) network to identify core targets. Functional analysis through Gene Ontology (GO) and KEGG pathway enrichment was performed. The key targets of Nagab-9 intervention in ALI were further validated in LPS-induced ALI mouse models and in mouse alveolar epithelial cell injury models. Results A total of 25 active components were identified from Nagab-9. PPI network analysis highlighted core targets, and GO and KEGG pathway analyses identified significant pathways involved. Six core components were selected based on topological parameters of the “compound-target-pathway-disease” network. In vivo, Nagab-9 was shown to alleviate ALI-induced lung damage, inhibit inflammatory infiltration, and modulate inflammatory factors by downregulating Ly6G, Cit-H3, and phosphorylated proteins SRC, ERK1/2, and STAT3 in lung tissue. In vitro experiments demonstrated that Nagab-9 effectively inhibits LPS-induced inflammatory responses, protecting lung tissue and suppressing neutrophil infiltration and NET formation, likely through the SRC/ERK1/2/STAT3 pathway. Conclusion Nagab-9 exerts a protective effect against ALI by modulating inflammatory responses and reducing neutrophil infiltration and NET formation, primarily via the SRC/ERK1/2/STAT3 signaling pathway. This study supports Nagab-9 as a promising therapeutic agent for ALI intervention.